2014
DOI: 10.4185/rlcs-2014-1000
|View full text |Cite
|
Sign up to set email alerts
|

Agenda y marcos en las webs de PP y PSOE en la cibercampaña de 2011

Abstract: Introducción: El impacto de las TIC sobre el modelo de comunicación política mediática ha otorgado una creciente centralidad a las webs partidistas en la estrategia de los partidos políticos, desde donde tratan de imponer su agenda en el espacio público. Objetivos y metodología: Este estudio propone un análisis integrado de a) la construcción de la agenda temática, b) el ataque al rival político y c) los frames de PP y PSOE en la campaña de 2011 a través de las noticias publicadas diariamente en sus sitios web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…Criticism is an emerging device in the communication strategy of political actors (RQ1). They regard Facebook as a vehicle to self-promote their figure while condemning adversaries, criticizing the defects, errors, and contradictions that they may have committed (D'Adamo and Beaudox 2016;Ceron and d'Adda 2016;Valera-Ordaz and López-García 2014). However, as the previous literature has shown, this dynamic does not appear as a consequence of the impact of the Internet and social media but was already present in the offline electoral campaigns (Mazzoleni 2010).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Criticism is an emerging device in the communication strategy of political actors (RQ1). They regard Facebook as a vehicle to self-promote their figure while condemning adversaries, criticizing the defects, errors, and contradictions that they may have committed (D'Adamo and Beaudox 2016;Ceron and d'Adda 2016;Valera-Ordaz and López-García 2014). However, as the previous literature has shown, this dynamic does not appear as a consequence of the impact of the Internet and social media but was already present in the offline electoral campaigns (Mazzoleni 2010).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the last decade, the consolidation of social media has favored its growth, thanks, among other factors, to the facilities for freedom of expression that these platforms offer. As happened on television, political actors use these digital media as a vehicle to highlight and amplify the adversary's past or present defects, errors, and contradictions, rather than highlighting their virtues (D'Adamo and Beaudox 2016;Ceron and d'Adda 2016;Valera-Ordaz and López-García 2014). In addition to criticizing the program, ideology, or trajectory of the opponent, there are other attacks based on arguments, both true and false, about his or her character or personal traits (Maier and Nai 2021;Stevens 2012;Lau and Pomper 2004).…”
Section: Negativity In the Electoral Campaign: From Television To Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…A content analysis is carried out of tweets published by the main leaders of the four political parties with the greatest representation in the Spanish parliament. As previous studies related to Twitter and political communication have shown, content analysis is the most suitable quantitative technique to determine and characterize the volume of tweets shared by the selected politicians (Valera Ordaz and López García, 2014; Cano-Orón and Llorca-Abad, 2017). A categories system has been designed to classify and characterize the tweets of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…The category system has five variables and a set of categories. The variables and categories were selected in line with previous studies on the qualitative and quantitative analysis of tweets (Valera Ordaz and López García, 2014;Cano-Orón and Llorca-Abad, 2017); studies that analyse online content in relation to feminism (Roca-Sales and López García, 2017; Fotopoulou, 2016; Sánchez-Duarte and Fernández-Romero, 2017); and research on communicative intentionality (Austin, 1962;Searle, 1969) as follows:…”
Section: Methodsmentioning
confidence: 99%